MCAT Preparation Guide - Willey, Miriam S.; Jarecky, Barbara M. (Book collections on Project MUSE., 1995)
Competition for admission to American medical schools has always been intense. Now, with more than 40,000 pre-med students applying for the few available slots each year, scoring well on the Medical College Admission Test (MCAT) is more critical than ever. The MCAT Preparation Guide offers students a systematic, sensible way to improve MCAT test scores. It recognizes their need to understand not only the subject areas covered but also the way the MCAT is structured and what test scorers look for. Extensively field tested at the University of Chicago, Tulane University, Howard University, and th.